2020
DOI: 10.1209/0295-5075/131/31003
|View full text |Cite
|
Sign up to set email alerts
|

Ring-like vortices in a logarithmic generalized Maxwell theory

Abstract: We investigate the presence of vortex structures in a Maxwell model with a logarithmic generalization. This generalization becomes important because it generates stationary field solutions in models that describe the dynamics of a scalar field. In this work, we will choose to investigate the dynamics of the complex scalar field with the gauge field governed by the Maxwell term. For this, we will investigate the Bogomol'nyi equations to describe the static field configurations. Then, we show numerically that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…This behavior of the magnetic field seems to occur due to the fact that the gauge field presents an exponentiallike behavior until it reaches the value −η 1 . We emphasize that the shape of solutions for the magnetic field has already been noted in other models [36] 3 Phase transitions and configurational entropy Configurational entropy is inspired by Shannon entropy which was proposed in 1948 [42]. Information in Shannon's communication theory is defined as…”
Section: Asymptotic Behavior and Numerical Solutionmentioning
confidence: 97%
See 1 more Smart Citation
“…This behavior of the magnetic field seems to occur due to the fact that the gauge field presents an exponentiallike behavior until it reaches the value −η 1 . We emphasize that the shape of solutions for the magnetic field has already been noted in other models [36] 3 Phase transitions and configurational entropy Configurational entropy is inspired by Shannon entropy which was proposed in 1948 [42]. Information in Shannon's communication theory is defined as…”
Section: Asymptotic Behavior and Numerical Solutionmentioning
confidence: 97%
“…[35] and with generalized models using Gausson-like logarithmic terms in Refs. [36,37]. It is worth noting that Gausson-like logarithmic potentials are interesting for describing quantum Bose liquids [38], and quantum gravity theory [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a logarithmic potential generates solitonic solutions in bidimensional models with logarithmic nonlinearity [29]. Recently, it has been observed that the logarithmic potential can generate ring-like vortices with intense magnetic flux when the Higgs field is coupled to the gauge field [30]. But, the first works on relativistic theories are due to G. Rosen [31,32], and to Bialynicki-Birula and Mycielski (BBM) in the context of Schrödinger theories [33].…”
Section: Introductionmentioning
confidence: 99%
“…[35] and with generalized models using Gaussonlike logarithmic terms in Refs. [36,37]. It is worth noting that Gausson-like logarithmic potentials are interesting for describing quantum Bose liquids [38], and quantum gravity theory [39].…”
Section: Introductionmentioning
confidence: 99%